Antimicrobial stewardship and drug formulary restrictions during COVID-19: what is restricted and who decides? - Alfredo J. Mena Lora; Rodrigo Burgos; Scott Borgetti; Lelia H. Chaisson; Susan C. Bleasdale (Cambridge University Press, 2023)
COVID-19 therapies were challenging to deploy due to evolving literature and conflicting guidelines. Antimicrobial stewardship can help optimize drug use. We conducted a survey to understand the role of stewardship and formulary restrictions during the pandemic. Restrictions for COVID-19 therapies were common and approval by infectious disease physicians often required.